A New Iron-Nanofluid as Fuel additive for Particulate Matter Reduction in Heavy Fuel Oil-Fired Boiler Facility - Kim, D.C.; Kim, J.H.; Woo, J.K.; Shin, D.H.; Lee, Y.S.; Kaushik, R.D. (Asian Journal of Chemistry, 2010)
Preparation and utilization method of a new Fe-nanofluid based heavy fuel oil additive for particulate matter reduction in heavy fuel oil fired boiler facilities have been presented and discussed. The nanofluid contained average particle size of 22 nm and is cost effective as it was prepared from industrial waste iron sulphate by simple methodology. The additive was found to reduce particulate matter by 53.3 % at an active metal concentration of 100 ppm without affecting the NOx content of flue gas significantly-a condition that is desirable for avoiding the trade-off between particulate matter and NOx emission which otherwise requires complex methodology. Proper explanations for the effects including the mechanism and reactions involved have also been discussed.